The impact of the COVID-19 pandemic on children and adolescent mental health inpatient service use in England: An interrupted time-series analysis of national patient records - A. Tsiachristas; J. Holland; B. Guo; K. Sayal; A. Pari (European Psychiatry, 2023)
Introduction During the COVID 19 pandemic children and young people (CYP) faced significant restrictions. The virus and restrictions also affected how health services could function, including mental health. Research analysing the COVID 19 pandemic is important to ensure dynamic and resilient service design in case of future national emergencies. Objectives To investigate the impact of COVID-19 lockdowns on CYP psychiatric admission trends during lockdowns 1 (started 26 March 2020) and 2 (started 20 November 2020) of the COVID 19 pandemic in England. Methods Routinely collected, retrospective, English, administrative data looking at the CYP hospital admissions, length of stay and patient demographics were analysed using an interrupted time series analysis to compare pre-pandemic service use with service use during COVID 19 lockdowns 1 and 2. The analysis used an ordinary least squares (OLS) approach with Newey–West standard errors to handle autocorrelation and heteroscedasticity. Results